High-Intensity Interval Training for Heart Failure Patients With Preserved Ejection Fraction (HIT-HF)-Rational and Design of a Prospective, Randomized, Controlled Trial - Gasser, Benedikt A.; Boesing, Maria; Schoch, Raphael; Brighenti-Zogg, Stefanie; Kröpfl, Julia M.; Thesenvitz, Elke; Hanssen, Henner; Leuppi, Jörg D.; Schmidt-Trucksäss, Arno; Dieterle, Thomas (Frontiers in Physiology, 2021)
Background: The pathophysiology of HF with preserved ejection fraction (HFpEF) has not yet been fully understood and HFpEF is often misdiagnosed. Remodeling and fibrosis stimulated by inflammation appear to be main factors for the progression of HFpEF. In contrast to patients with HF with reduced ejection fraction, medical treatment in HFpEF is limited to relieving HF symptoms. Since mortality in HFpEF patients remains unacceptably high with a 5-year survival rate of only 30%, new treatment strategies are urgently needed. Exercise seems to be a valid option. However, the optimal training regime still has to be elucidated. Therefore, the aim of the study is to investigate the effects of a high-intensity interval (HIT) training versus a moderate continuous training (MCT) on exercise capacity and disease-specific mechanisms in a cohort of patients with HFpEF. Methods: The proposed study will be a prospective, randomized controlled trial in a primary care setting including 86 patients with stable HFpEF. Patients will undergo measurements of exercise capacity, disease-specific blood biomarkers, cardiac and arterial vessel structure and function, total hemoglobin mass, metabolic requirements, habitual physical activity, and quality of life (QoL) at baseline and follow-up. After the baseline visit, patients will be randomized to the intervention or control group. The intervention group (n=43) will attend a supervised 12-week HIT on a bicycle ergometer combined with strength training. The control group (n=43) will receive an isocaloric supervised MCT combined with strength training. After 12 weeks, study measurements will be repeated in all patients to quantify the effects of the intervention. In addition, telephone interviews will be performed at 6 months, 1, 2 and 3 years after the last visit to assess clinical outcomes and QoL. Discussion: We anticipate clinically significant changes in exercise capacity, expressed as VO2peak, as well as in disease-specific mechanisms following HIT compared to MCT. Moreover, the study is expected to add important knowledge on the pathophysiology of HFpEF and the clinical benefits of a training intervention as a novel treatment strategy in HFpEF patients, which may help to improve both QoL and functional status in affected patients.